Modern Model of Competences of Personal Agents as Increase Factor of Clients’ Subjective Well-being; Procedia - Social and Behavioral Sciences; Vol. 166 : Proceedings of The International Conference on Research Paradigms Transformation in Social Sciences 2014 (RPTSS-2014), 16–18 October 2014, Tomsk, Russia - Kiseleva E. S. Elena Stanislavovna (2015, 2015)
Title screen